From block clearance to sprint running: Characteristics underlying an effective transition - Debaere, S.; Delecluse, C.; Aerenhouts, D.; Hagman, F.; Jonkers, I. (Journal of Sports Sciences, 2013)
The aim of this study was to characterize the specifics of the sprint technique during the transition from start block into sprint running in well-trained sprinters. Twenty-one sprinters (11 men and 10 women), equipped with 74 spherical reflective markers, executed an explosive start action. An opto-electronic motion analysis system consisting of 12 MX3 cameras (250 Hz; 325,000 pixels) and two Kistler force plates (1000 Hz) was used to collect the three-dimensional (3D) marker trajectories and ground reaction forces (Nexus, Vicon). The 3D kinematics, joint kinetics, and power were calculated (Opensim) and were time normalized to 100% from the first action after gunshot until the end of second stance after block clearance (Matlab). The results showed that during the first stance, power generation at the knee plays a significant role in obtaining an effective transition, representing 31% of power generation in the lower limb, in the absence of preceding power absorption. Furthermore, the sprinter actively searches a more forward leaning position to maximize horizontal velocity. Since success during sprinting from the second stance onwards involves high hip and ankle activation, the above-mentioned three characteristics are specific skills required to successfully conclude the transition from start block into sprint running.